Antiepileptic drugs as objects of the national pharmaceutical market. Message II. Analysis of economic availability of antiepileptic drugs (on the example of assortment offers of top-3 wholesale pharmaceutical enterprises of Ukraine) - Genyk, Pavlo; Levitsky, Oxana; Chukhray, Iryna; Yarko, Nataly; Tereschuk, Sophia; Hromovik, Bogdan (Annals of Mechnikov’s Institute, 2023)
Introduction. Epilepsy is one of the most common neurological diseases in the world and requires appropriate medical treatment. The Global Burden of Epilepsy Report estimates that there are 13 million disability adjusted life years due to epilepsy each year. Epilepsy is an important medical, social and economic problem of modern society, the solution of which is often based on the use of antiepileptic drugs. According to the State Strategy for the implementation of the state policy of providing the population with medicines for the period until 2025, the cost of medicines is an important factor that ensures their financial availability for the population. This determined the relevance of this stage of the research. Material & methods. Materials: information about purchase prices (Pp) for antiepileptic drugs of wholesale pharmaceutical enterprises (WPE 1, WPE 2 and WPE 3), which at the time of the study were in the TOP-3 in terms of the volume of drug supplies to pharmacies. Methods: information search, comparison, analysis, generalization, determination of the cost of defined daily dose (DDD). The study period was February 2023. Results & discussion. It was found that at the time of the research, the TOP-3 WPE offered 105 assortment items (AI) of 11 international non-proprietary names of antiepileptic drugs in their price lists, taking into account the dosage forms and doses. By studying the DDD Pp of antiepileptic drugs AI, it was established that the largest number of AI with the lowest DDD Pp was offered by WPE 1 – 34 AI (or 32.38% of the total number of analyzed drugs). At the same time, in 26 AI (24.76%) offered by WPE 2, the cost of DDD was lower than that of competitors. The most valuable were the offers of WPE 3. It was found that among the 36 AI of pregabalin, the lowest DDD Pp was inherent in 15 and 8 AI, offered by WPE 1 and WPE 2, respectively. The price range of AI pregabalin DDD ranged from UAH 18.60 (“Pregabalin-Darnytsia”, capsules 300 mg No. 21, PJSC Pharmaceutical company Darnytsia (Ukraine), the lowest price offer of WPE 1) to UAH 58.28 (“Galara”, capsules 75 mg No. 14, WORLD MEDICINE İLAÇ SAN. VE TİC. A.Ş. (Turkey), the highest price offer of WPE 3). The calculated values of Cliq ranging from 0.002 to 0.17 and Iаv from 5.68% to 17.21% for AI of pregabalin indicate a high level of competition and relative economic availability of the analyzed antiepileptic drugs in the studied segment of the wholesale market. At the same time, using the matrix projection of the integrated Sliq / Iav analysis, 7 or 19.44% of pregabalin AI were determined, which were the most economically available in the TOP-3 offers of the WPE. Conclusion. A situational analysis of the economic availability of antiepileptic drugs was carried out on the example of assortment offers of the TOP-3 wholesale pharmaceutical enterprises of Ukraine. Keywords: Еpilepsy, antiepileptic drugs, wholesale pharmaceutical enterprises, cost of DDD, price liquidity ratio, indicator of economic availability